A review of solar-driven short-term low temperature heat storage systems. (May 2021) - Shen, Yongliang; Liu, Shuli; Mazhar, Abdur Rehman; Han, Xiaojing; Yang, Liu; Yang, Xiu'e
Abstract: This article reviews three types of solar-driven short-term low temperature heat storage systems – water tank heat storage, phase change materials heat storage and thermochemical heat storage. The objective of this study is to comprehensively compare three heat storage systems, and put forward the future research direction, so as to provide guidance for researchers. This article compares the heat storage principles, research status and key parameters of these three systems, and makes a brief economic assessment to evaluate the possibility and schedule of application. Finally, the future research directions are proposed. This review shows that the performance of the water tank heat storage system is mainly affected by the structural parameters of the water tank. The phase change material heat storage system is more affected by the thermal performance parameters of the material itself. Thermochemical heat storage pays attention to the material thermal performance parameters and the reaction bed structure parameters at the same time. From an economic point of view, water tank heat storage is completely feasible in the global market. The application prospect of phase change material heat storage in moderate climates is obviously stronger than that of tropical climates, while the thermochemical heat storage system can be economically feasible around 2030. The main directions for future studies of the three systems are established such as using two or more water tanks for heat storage, developing cascaded phase change material heat storage system, mathematical model and optimization theory, combining two or three systems for cascaded utilization of solar energy. Highlights: Key parameters of each heat storage system are obviously different. Economic assessment is used to evaluate the possibility for the applications. Future research directions based on research status. The suggested combination system can improve the thermal performance.